Study on Thermoelectric Generators Based on Exhaust Gas and Cryogenic Fuel for LNG Vehicles - 郑江; 厉彦忠; 王春燕; 谭宏博 (Zhileng xuebao, 2014)
To enhance the energy efficiency in the liquefied natural gas (LNG) vehicles, thermoelectric generator (TEG) is suggested in recovering the waste heat of the exhaust gas (EG) and the cold energy of the LNG. The TEGs here get higher efficiency than conventional ones, for they work with heat sinks at cryogenic temperatures and there are large temperature differences between EG and LNG. Based on the analyzing of the typical fuel system in the small LNG vehicles, two recovery systems for the LNG vehicles are proposed and the correlative parameters of systems are calculated and analyzed. The generation efficiency of TEGs is calculated and the recovery power of each system is analyzed. It is concluded that the output power of the vaporizer system is larger than that of the self-warming system; TEG with optimized multi-layer material brings larger output power than that with single-layer material for both systems.